Walking Hand in Hand : Fiscal Policy and Growth in Advanced Economies - Jaramillo, Laura (IMF Working Papers; Working Paper ;, 2012)
Implementation of fiscal consolidation by advanced economies in coming years needs to take into account the short and long-run interactions between economic growth and fiscal policy. Many countries must reduce high public debt to GDP ratios that penalize longterm growth. However, fiscal adjustment is likely to hurt growth in the short run, delaying improvements in fiscal indicators, including deficits, debt, and financing costs. Revenue and expenditure policies are also critical in affecting productivity and employment growth. This paper discusses the complex relationships between fiscal policy and growth both in the short and in the long run.